Meningkatkan Prestasi Belajar Siswa Kelas IX pada Materi Bangun Sisi Lengkung Melalui Metode Demonstrasi - Neyim` Neyim (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2018)
The purpose of this study was to determine whether the use of demonstration methods in curved side material can improve student learning achievement. The type of research used in this study is Class Action Research. Data collection used observation sheets, critical thinking tests and cognitive learning outcomes. Learning in the first cycle, student learning achievement averaged 62.72 and in the first cycle that was completed there were 12 students (48%), which did not complete 13 students (52%). In learning in the second cycle, student learning achievements averaged 77.48 and in the second cycle were completed there were 16 students (64%) and those who did not complete there were 9 students (36%). It was concluded that there was an increase in student learning achievement from the first cycle to the second cycle. Thus the Demonstration method can improve the learning achievement of class IX students on the material of the curved side.